Projected changes to Arctic shipping routes after stratospheric aerosol deployment in the ARISE-SAI scenarios - Morrison, Ariel L.; Pathak, Debanjali; Barnes, Elizabeth A.; Hurrell, James W. (Frontiers in Climate, 2024)
IntroductionRapid reductions in Arctic sea ice in response to warming have led to increased interest in using the Arctic Ocean for commercial shipping. As the world warms, however, different strategies are being considered to stabilize or reduce surface temperatures in order to prevent critical climate change impacts. One such strategy is stratospheric aerosol injection (SAI), a form of solar climate intervention. Projected changes to Arctic sea ice under SAI with specific regards to shipping have not yet been assessed.MethodsWe compare output from two SAI simulations that have different global mean temperature targets with a non-SAI control simulation to provide the first assessment of Arctic Ocean navigability under potential SAI scenarios.ResultsWe find that sea ice concentration and thickness quickly stabilize or increase after SAI deployment. When sea ice thickness stabilizes in response to SAI, the number of days when the Arctic Ocean is navigable remains fairly constant, but increasing sea ice thickness leads to reduced navigability compared to the non-SAI simulation. From 2035-2069, both the Northwest Passage and Northern Sea Route are accessible from July-November in all three simulations, but there are no navigable routes under either SAI scenario from April-June. When the Arctic is navigable, it can take 2-12 days longer to cross the Arctic Ocean in the SAI simulations than in the non-SAI control simulation, and there are large year-to-year variations in travel time.DiscussionOverall, Arctic shipping may take longer and be more difficult in an SAI vs a non-SAI world because of relatively thicker sea ice, but the degree to which Arctic shipping may change in response to SAI is dependent on the particular climate intervention strategy.